Pohlia Hedw. section Pohlia (Bryaceae) in Central and South America - Suarez, Guillermo Martin (2011)
Pohlia section Pohlia is taxonomically revised for Central and South America. Five species are recognized in the study area (P. cruda, P. elongata, P. longicollis, P. nutans, and P. oerstediana). Seven new synonyms are proposed. Pohlia leptopoda, Webera grammocarpa, and W. crassicostata from Brazil, P. rusbyana, and P. subleptopoda from Bolivia, and P. leptodontium from Colombia are synonyms of P. elongata. P. elatior from New Zealand is a synonym of P. nutans. Eight new lectotypes are designated. Pohlia oerstediana is a new record to South America and the extension ranges of Latin American species are presented. All Neotropical species of Section Pohlia are described and illustrated and distribution maps are given.